Making STEAM-Based Professional Learning: A Four-Year Design-Based Research Study - Janette Hughes; Laura Morrison; Jennifer Robb (The Canadian Network for Innovation in Education (CNIE), 2022)
This article reports on the evolution of a STEAM-based teacher professional learning program designed to focus on maker pedagogies. Design-Based Research methodology was used to frame three iterations of professional learning sessions, which collectively involved more than 85 teachers in Ontario, Canada. The article describes the three iterations of teacher professional learning related to a maker approach, reports on what we learned from each iteration and how we modified the pedagogical approach based on the findings, and includes discussion on the implications for future professional learning in maker education.